Theoretical insights for generation of terminal metal-oxo species and involvement of the "oxo wall". (18th August 2022) - Monika,; Aman,; Ansari, Azaj
Abstract : This work is based on a deep insight on the formation of high-valent metal-oxo by the O⋯O bond cleavage of metal hydroperoxo species and our theoretical findings also illustrate the concept "oxo wall". Abstract : Calculations based on density functional theory were undertaken for formation of terminal metal-oxo from metal hydroperoxo species with buea ligand. The energy barriers for cleavage of the O⋯O bond were higher for late transition metals than early transition metals, which unveiled formation of the "oxo wall". Our computed structural correlations also supported the concept of the oxo wall.